Lopinavir/ritonavir combination therapy amongst symptomatic coronavirus disease 2019 patients in India: Protocol for restricted public health emergency use - Bhatnagar, Tarun (Indian J Med Res, 2020)
As of February 29, 2020, more than 85,000 cases of coronavirus disease 2019 (COVID-19) have been reported from China and 53 other countries with 2,924 deaths. On January 30, 2020, the first laboratory-confirmed case of COVID was reported from Kerala, India. In view of the earlier evidence about effectiveness of repurposed lopinavir/ritonavir against severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) coronavirus (CoV), as well as preliminary docking studies conducted by the ICMR-National Institute of Virology, Pune, the Central Drugs Standard Control Organization approved the restricted public health use of lopinavir/ritonavir combination amongst symptomatic COVID-19 patients detected in the country. Hospitalized adult patients with laboratory-confirmed SARS-CoV-2 infection with any one of the following criteria will be eligible to receive lopinavir/ritonavir for 14 days after obtaining written informed consent: (i) respiratory distress with respiratory rate ≥22/min or SpO(2) of <94 per cent; (ii) lung parenchymal infiltrates on chest X-ray; (iii) hypotension defined as systolic blood pressure <90 mmHg or need for vasopressor/inotropic medication; (iv) new-onset organ dysfunction; and (v) high-risk groups - age >60 yr, diabetes mellitus, renal failure, chronic lung disease and immunocompromised persons. Patients will be monitored to document clinical (hospital length of stay and mortality at 14, 28 and 90 days), laboratory (presence of viral RNA in serial throat swab samples) and safety (adverse events and serious adverse events) outcomes. Treatment outcomes amongst initial cases would be useful in providing guidance about the clinical management of patients with COVID-19. If found useful in managing initial SARS-CoV-2-infected patients, further evaluation using a randomized control trial design is warranted to guide future therapeutic use of this combination.